A comparative analysis on digital libraries and academic search engines from the dual-route perspective. Issue 2 (15th June 2021) - Cao, Fenfang; Zhang, Jinchao; Zha, Xianjin; Liu, Kunfeng; Yang, Haijuan
Abstract : Purpose: Digital libraries and academic search engines have developed as two important online scholarly information sources with different features. The purpose of this study is to compare digital libraries and academic search engines from the perspective of the dual-route model. Design/methodology/approach: Research hypotheses were developed. Potential participants were recruited to answer an online survey distributing at Chinese social media out of which 251 responses were deemed to be valid and used for data analysis. The paired samples t -test was used to compare the means. Findings: Both information quality (central route) and source credibility (peripheral route) of digital libraries are significantly higher than those of academic search engines, while there is no significant difference between digital libraries and academic search engines in terms of affinity (peripheral route). Practical implications: In the digital information society, the important status of digital libraries as conventional information sources should be spread by necessary measures. Academic search engines can act as complementary online information sources for seeking academic information rather than the substitute for digital libraries. Practitioners of digital libraries should value the complementary role of academic search engines and encourage users to use academic search engines while emphasizing the importance of digital libraries as conventional information sources. Originality/value: According to the dual-route model, this study compares digital libraries and academic search engines in terms of information quality, source credibility and affinity, which the authors believe presents a new lens for digital libraries research and practice alike.